The Level of Intensity of Bullying Behavior Using Quantitative Descriptive Research Methods at State Elementary School 008/VII Rangkiling Simpang 1 - Sutrisno Sutrisno (FKIP - Universitas Riau, 2026)
This study aims to identify the intensity of bullying behavior that occurs at SD Negeri 008/VII Rangkiling Simpang 1 using a quantitative descriptive method approach. Bullying is a deviant behavior that can have a negative impact on children's social and psychological development, especially at the elementary school level. This study involved 60 students from grades I to VI who were selected using a saturated sampling technique. The data collection instrument was a closed questionnaire that included several indicators of bullying forms, such as physical bullying, verbal bullying, relational bullying, and cyberbullying. The collected data were analyzed descriptively using percentages to describe the level of intensity of each type of bullying. The results showed that verbal bullying had the highest level of intensity compared to other forms of bullying, followed by relational bullying, physical bullying, and finally cyberbullying. These findings emphasize the important role of schools and parents in creating a safe and comfortable educational environment that supports students' social and emotional development.